Ekstraksi Rimpang Jahe: Mengungkap Khasiat dari Metode Dekok dan Infusa - Anwar, Yelfi; Fikri, Muhammad Sayid Ali; Rahmadani, Nur Fitri; Ikramullah, Nazwa; Permatasari, Nurfebby; Rahmah, Siti; Istiqomah, Fajriatul; Regina, Regina; Surahman, Dziki Dzikrivan (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Ginger (Zingiber officinale Roscoe) is a medicinal plant widely used in traditional medicine in Indonesia due to its diverse active compounds. However, many people still do not understand the proper extraction methods to maximize the recovery of beneficial compounds from ginger rhizomes. This community service activity aims to improve community knowledge and skills in processing ginger through decoction and infusion methods. The methods used included interactive counseling and live demonstrations on the preparation of herbal remedies, extraction techniques, and the advantages and disadvantages of each method. As part of the evaluation, pre- and post-tests were conducted to measure participants' understanding. The results showed an average pre-test score of 92.89, which increased to 96.67 in the post-test. This increase indicates that the counseling activity successfully strengthened participants' understanding, both theoretically and practically. This activity demonstrates that an experiential educational approach can have a positive impact on increasing public literacy regarding the use of medicinal plants.